PSYCHIATRIC DEINSTITUTIONALIZATION IN BRAZIL: THE ROLE OF THERAPEUTIC RESIDENCES AND THE IMPORTANCE OF THE FAMILY HEALTH STRATEGY - Costa Silva, Lays (Health and Society, 2024)
The Brazilian Psychiatric Reform is a movement that seeks to transform the mental health care model, promoting the deinstitutionalization and social inclusion of people with mental disorders. In this context, Therapeutic Residences represent an alternative to psychiatric institutionalization, offering residential support for individuals who face these disorders and need family or community support, aiming for their social reintegration. This experience report seeks, therefore, to share the experience of a team from the Family Health Strategy in the city of Rio de Janeiro-RJ after one year of monitoring residents of a Therapeutic Residence.